Strategi Manajemen Risiko dalam Industri Pelayaran untuk Meningkatkan Keamanan dan Efisiensi Operasional: Strategi Manajemen Risiko dalam Industri Pelayaran untuk Meningkatkan Keamanan dan Efisiensi Operasional - supangat, supangat (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2024)
ABSTRACT This research aims to investigate risk management strategies implemented in the shipping industry with a focus on improving safety and operational efficiency. Through comprehensive qualitative and quantitative analysis approaches, as well as a combination of methods, including in-depth interviews, surveys, and document analysis. This research identifies the main risks faced by shipping companies and evaluates the effectiveness of the risk management strategies that have been implemented. The research results highlight the importance of the use of advanced technology, cooperation with maritime authorities, and a strong safety culture as key elements in improving a company's safety and operational performance. The research recommendations include steps for further improvement, including more specific risk analysis, research into regulatory changes, and further employee training. By understanding and implementing appropriate risk management strategies, shipping companies can reduce the risks they face and improve their operational performance amidst the ever-growing challenges in the maritime environment. The implications of the results of this research strengthen understanding of the importance of risk management in improving the safety and operational performance of shipping companies. Keywords: Risk management, shipping industry, security and operational efficiency.